2020
DOI: 10.1021/acs.energyfuels.9b04067
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery in High Salinity and Elevated Temperature Conditions with a Zwitterionic Surfactant and Silica Nanoparticles Acting in Synergy

Abstract: Novel SiO2 nanoparticles (NPs) costabilized by a low-molecular-weight ligand (steric stabilization) and a zwitterionic surfactant (electrostatic stabilization) were developed for enhanced oil recovery purpose in sandstone reservoirs with high salinity and elevated temperatures. According to our experiments, the proposed NPs were not sensitive to either monovalent or divalent cations, whose size remained around 10.0 nm in API brine within 8 weeks at 25 °C and 4 weeks at 60 °C. Using the zwitterionic surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, the applications of nanofluids in HTHS conditions are still limited and nanofluids with higher thermal and salt resistance should be developed. To improve the stability of NPs, ligands with dendritic structure or copolymers can be used (Zuniga et al, 2016;Zhong et al, 2020), but particle size should be carefully screened, and smaller particles are better preferred. 4) Structural disjoining pressure is proposed as the underlying mechanism in most studies to explain the wettability alteration by nanofluids by simply drawing a schematic diagram without compelling substantial evidence.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…However, the applications of nanofluids in HTHS conditions are still limited and nanofluids with higher thermal and salt resistance should be developed. To improve the stability of NPs, ligands with dendritic structure or copolymers can be used (Zuniga et al, 2016;Zhong et al, 2020), but particle size should be carefully screened, and smaller particles are better preferred. 4) Structural disjoining pressure is proposed as the underlying mechanism in most studies to explain the wettability alteration by nanofluids by simply drawing a schematic diagram without compelling substantial evidence.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Xu et al, Cheraghian et al, Haeri et al, Songolzadeh and Moghadasi, Zhao et al, and Zhong et al. have shown that the combinations of silica nanoparticles with different surfactants have a good potential to alter wettability from oil-wet to water-wet. Suleimanov et al showed that nonferrous metal NPs can reduce IFT/surface tension . Mohajeri et al, by combining ZrO 2 NPs with sodium dodecyl sulfate and CTAB, showed that the nanofluids optimize IFT/surface tension and alter wettability …”
Section: Introductionmentioning
confidence: 99%
“…Mohajeri et al, by combining ZrO 2 NPs with sodium dodecyl sulfate and CTAB, showed that the nanofluids optimize IFT/surface tension and alter wettability Table S2 summarizes the studies on the synergistic effects of nanosurfactants. …”
Section: Introductionmentioning
confidence: 99%
“…prepared hydrophobic silica nanoparticles by surface modification of silica nanoparticles with dimethyldichlorosilane. The result showed that the modified silica nanoparticles are adsorbed on the surface of the core and form a hydrophobic layer, changing the wettability of the sand surface from water wet to oil wet, thereby decreasing the flowing pressure . Gao et al established a set of biological nanomaterial depressurization and injection-augmenting numerical simulation technology water flooding models that consider the adsorption characteristics and reservoir physical properties.…”
Section: Introductionmentioning
confidence: 99%